Taxonomic revision of the genus Lycenchelys (Osteichthyes: Zoarcidae) in Japanese waters - Kawarada, Shumpei; Imamura, Hisashi; Narimatsu, Yoji; Shinohara, Gento (Zootaxa, 2020)
Eelpout species of the genus Lycenchelys Gill, 1884 recorded from Japanese waters are taxonomically revised. This study recognizes the following 11 species from Japanese waters as valid: Lycenchelys albomaculata Toyoshima, 1983, Lycenchelys aurantiaca Shinohara & Matsuura, 1998, Lycenchelys hippopotamus Schmidt, 1950, Lycenchelys maculata Toyoshima, 1985, Lycenchelys makushok Fedorov & Andriashev, 1993, Lycenchelys melanostomias Toyoshima, 1983, Lycenchelys rassi Andriashev, 1955, Lycenchelys remissaria Fedorov, 1995, Lycenchelys ryukyuensis Shinohara & Anderson, 2007, Lycenchelys squamosa Toyoshima, 1983 and Lycenchelys tohokuensis Anderson & Imamura, 2002. We redescribe species in detail based on type specimens as well as additional specimens in many cases. The synonymy of Lycenchelys brevimaxillaris Toyoshima, 1985 with L. melanostomias is supported in this study. Sexual dimorphism and changes with growth are revealed in L. albomaculata, L. aurantiaca, L. hippopotamus, L. makushok, L. melanostomias and L. rassi, all based on 10 or more specimens, for relative head length, head width, and upper and lower jaw lengths. In addition, we also found that the sizes at which sexual dimorphism can be recognized, and the tendencies for change with growth, differ among species. Furthermore, the dimorphism in head length is influenced by the snout length, eye diameter and/or postorbital length in L. albomaculata and L. aurantiaca.